Creating a User-Based Website to Support Academic Integrity at the University of Waterloo - Nearing, Erin (Canadian Perspectives on Academic Integrity, 2020)
The University of Waterloo identified a redesign of their existing academic integrity website as an important step in creating a culture of integrity on campus. This article details how the new website supports students, instructors, and staff by utilizing best practises and approaches suggested in academic integrity research. Next steps will include exploring how to increase engagement with the site and determining the impact of the site on the campus community.